2014
DOI: 10.1136/thoraxjnl-2014-205429
|View full text |Cite
|
Sign up to set email alerts
|

Coarse particulate matter associated with increased risk of emergency hospital admissions for pneumonia in Hong Kong

Abstract: Background Epidemiological research on the effects of coarse particles (PM c , particulate matter between 2.5 and 10 μm in aerodynamic diameter) on respiratory morbidity is sparse and inconclusive. Pneumonia is an inflammatory condition of lung caused by infections, which may be triggered and exacerbated by PM c exposure. Aim To estimate the effect of PM c on emergency hospital admissions for pneumonia after controlling for PM 2.5 and gaseous pollutants. Method PM c concentrations were estimated by subtracting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 33 publications
(41 reference statements)
6
52
2
Order By: Relevance
“…Similar to the findings of other studies (Qiu et al 2014;Yang et al 2012), higher risks due to the PM 10 exposure were observed for females and elderly individuals, and these individuals appear to be more vulnerable. However, the stratification differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the findings of other studies (Qiu et al 2014;Yang et al 2012), higher risks due to the PM 10 exposure were observed for females and elderly individuals, and these individuals appear to be more vulnerable. However, the stratification differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the magnitude of the health effect of particulate matter differs substantially across regions and countries (Medina-Ramon et al 2006). Due to expense of the equipment and limitations related to using personal exposure monitors for long periods of time on large numbers of people, previous studies have mainly used the average concentration of air pollutants from single or limited monitoring stations as the population exposure levels (Meng et al 2013;Qiu et al 2014;Qiu et al 2012;Tsai et al 2013;Yang et al 2005). This approach may result in inaccuracies, specifically exposure misclassification, and a consequent underestimation of the health effect estimates.…”
Section: Introductionmentioning
confidence: 96%
“…Exploring the potential effect modifiers is helpful to identify potentially susceptible population and to develop a more accurate targeted intervention. We found that the effects of PM 2.5 were significantly greater in the elderly people, which are consistent with previous findings [6,35,38]. These evidences suggested that elderly people, especially those presenting with COPD, should limit outdoor activity or wear a face mask outdoors to reduce personal exposure when PM 2.5 pollution is severe.…”
Section: Discussionsupporting
confidence: 82%
“…In spite of this, relatively few studies of ambient air pollution and respiratory infection have focused on early childhood, especially for young children in China (Qiu et al, 2014;Le et al, 2012).…”
Section: Introductionmentioning
confidence: 99%